Oligo-Carrageenans Induce a Long-Term and Broad-Range Protection Against Pathogens in Tobacco Plants (Var. Xanthi) - Moenne-Munoz, A; Contreras-Arredondo, R; Gonzalez-Figueroa, A (2012)
Here, we analyzed the effect of oligo-carrageenans kappa, lambda and iota on protection against tobacco mosaic virus (TMV), . Botrytis cinerea Whetzel and . Pectobacterium carotovorum Waldee and suppression of infections in tobacco plants. Treatment with increasing concentrations of oligo-carrageenans, increasing number of treatments and increasing time after treatment enhanced protection against TMV indicating a long-term protection that mimics vaccination, mainly oligo-carrageenan lambda. In addition, oligo-carrageenans induced protection against . P. carotovorum with similar efficiencies and against . B. cinerea, mainly oligo-carrageenans lambda and iota. Moreover, oligo-carrageenans induced a partial suppression of TMV and . P. carotovorum infections and a complete suppression of . B. cinerea infection at systemic level. Furthermore, oligo-carrageenans induced a sustained activation of phenylalanine ammonia lyase activity and the accumulation of phenylpropanoid compounds with potential antimicrobial activities suggesting these compounds are involved in protection and suppression effects. © 2012 Elsevier Ltd.